Analisis Aerodinamika Pada Pesawat Tanpa Awak Serindit V-2 Menggunakan Metode Komputasional Dinamika Fluida - Soegihin, Agung; Asral, Asral; Anuar, Kaspul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Serindit V-2 is an unmanned aircraft by the Serindit Aero UAV research team. It has the ability to fly rapidly in order to compete in KRTI in the Racing Plane division. Although it has been successfully produced and able to fly, comprehensive research on aerodynamic of Serindit V-2 aircraft flying behavior has never been done before. Aerodynamic research need to be conducted to improve the aircraft performance such as flying capability, air resistance efficiency and etc. This study aims to determine the value of flow characteristic such as coefficient of drag, lift, moment and pressure distribution based on fluid flow that occurs in the aircraft with variations of Angle of Attack and air velocity. The method used is CFD (Computational Fluid Dynamic) which is a computer-based numerical method and performed with an iterative procedure to predict aerodynamic characteristics and fluid flow phenomena on the aircraft surface. Simulations were carried out using Ansys Fluent software on the Serindit V-2 aircraft model sourced from the Serindit Aero Team. The result of the lift coefficient value is CLo = 0.3666 and CLMax value = 1.42626 at Î± 13o. The CDo obtained was 0.0589258. While the CMo value obtained is -8.34 x 10-5.Keyword: Flow Characteristics, CFD, Ansys Fluent